PEMANFAATAN BIJI MIMBA (AZADIRACHTA INDICA) SEBAGAI LARVASIDA NYAMUK CULEX SP. - RAHMAWATI, ELMA (LenteraBio: Berkala Ilmiah Biologi, 2013)
Environmentally friendly plant-based insecticides can be used incontrolling and preventing diseases caused by the Culex sp. mosquito. One of the alternative natural insecticide materialsare neem seeds (Javanese: Mimba). This study aimed to: 1). describe the effect of neem seed extract on the mortality of mosquito larvae Culex sp. 2). describe the concentrations of neem seed extract that cause mortality of mosquito larvae Culex sp.: 50% and 90%. This research was an experimental study. The larvae of Culex sp. of third instar obtained from ITD Airlangga University in Surabaya. This study used of completely randomized design with four treatments of neem seed extract concentration of 0.01%, 0.02%, 0.1%, 0.2%, 0.4% and controls with five times the repeatitions. Each treatment consisted of 20 larvae. Data were analyzed using Probit Regresion and Pearson Correlation. The results showed that the concentration of exctract that caused 50% mortality of mosquito larvae Culex sp. was 0.07172%, while the concentration of extract that caused 90% mortality larvae was 0.1927%. Pearson correlation analysis obtained the value of r = 0.922, which means that there was significant correlation between the concentrations of neem seed extract against mosquito larvae mortality of third instar Culex sp.   Key words: neem seed extract (Azadirachtaindica); mortality; Culex sp.